Conversational Agents as Full-Pledged BDI Agents for Ambient Intelligence - Mustapha A.; Ahmad M.S.; Ahmad A. (Springer Verlag, 2023)
The need for conversational agents based on the Belief-Desire- Intention (BDI) architecture rise to support natural interfaces in many application areas of ambient intelligence, among which are the smart homes, health monitoring and assistance, care for the elderly, transportation, education, and tourism. The objective of this paper is to present an implementation of a conversational agent as a full-pledged BDI agent. This is achieved through mapping the BDI constructs in intelligent agents to the natural language processing components in a classic conversational agent, Eliza. Discussions focus on the process of reengineering the conversational agent technologies into BDI approach. Springer International Publishing Switzerland 2013.